„O miłości! Cóż mogę o tobie powiedzieć?” Hugona ze św. Wiktora pochwała miłości - Zembrzuski, Michał (Studia Theologica Varsaviensia, 2018)
„Oh Love! What can I tell about you?”. The praise of the love in the works of Hugh of St. Victor Summary Hugh of St. Victor was one of the most important theologians, exegetes, educators and mystics in the twelfth century. One of the topics which he undertook was the value of love. In his very short, but very influential works, he expressed an extraordinary praise of love. Love is defined by him as both a road, as the one who accompanies the road, and also as the purpose of the road. Love is an agent which equates divine and human reality, because only in this way man can be saved and his happiness fully realized. Recognition the law of God and justice is effect of the faith, but their realization is the works of love. Although the approach of love has its source in St. Augustine, however, the main focus of it is the categories of running and rest (cursus et requies), and not the category of inclination or impetus (pondus).